1986
DOI: 10.1007/bf01283622
|View full text |Cite
|
Sign up to set email alerts
|

Attribute preferences and the non-metropolitan migration decision

Abstract: Interviews with recent migrants to several small nonmetropolitan places elicited attributes of ideal, origin and chosen settlements.Their responses permitted construction of simple measures or valuations of economic, social, individual and environmental aspects of ideal, origin and destination. From these it was possible to evaluate the critical components of the migration decision, to estimate tradeoffs between economic and noneconomic benefits, and to distinguish between probable movers and non-movers.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Ullman (1954) was among the first to cite amenities as a major Downloaded by [University Library Utrecht] at 06:19 17 March 2015 factor in the regional growth process. Since then, a number of studies have shown amenities to be an important factor in the migration process (Cushing, 1987;Frederick, 1985;Graves, 1979Graves, , 1983Morrill, Downing and Leon, 1986;Rudzitis, 1979Rudzitis, , 1989Rudzitis and Johansen, 1988;Swanson, 1986). Today it is recognized that people move and places increase or decrease in population because of a complex combination of factors.…”
Section: Migration Into Nonmetropolitan Areasmentioning
confidence: 95%
See 2 more Smart Citations
“…Ullman (1954) was among the first to cite amenities as a major Downloaded by [University Library Utrecht] at 06:19 17 March 2015 factor in the regional growth process. Since then, a number of studies have shown amenities to be an important factor in the migration process (Cushing, 1987;Frederick, 1985;Graves, 1979Graves, , 1983Morrill, Downing and Leon, 1986;Rudzitis, 1979Rudzitis, , 1989Rudzitis and Johansen, 1988;Swanson, 1986). Today it is recognized that people move and places increase or decrease in population because of a complex combination of factors.…”
Section: Migration Into Nonmetropolitan Areasmentioning
confidence: 95%
“…There are still millions of people in metropolitan areas who report on national surveys they would prefer to live in nonmetropolitan areas (Beale, 1988). What will happen in the future is difficult to project because the migration patterns and population distribution in the 1970s differed substantially from the pattern of earlier decades (Morrill, 1988;Odland, 1988). Morrill (1988) finds a typology of migration regions and states that reflects a transition from core to periphery in migration behavior.…”
Section: Migration Into Nonmetropolitan Areasmentioning
confidence: 97%
See 1 more Smart Citation
“…Dissatisfaction with one's place or community is a driving force in his/her decision to move (Heaton et al, 1981;Speare et al, 1982;Ge & Hokao, 2006). The potential migrants in some sense estimate the "expected utility" of the move (Morrill, et al, 1986), and people view the migration decision as one of utility maximization, i.e., they migrate in order to become better off in some subjective sense (Ziegler & Britton, 1981). In addition, the quality of life has a substantial impact on in-migration volumes to metropolis (Porell, 1982).…”
Section: Concept Of Expectations For the Future Lifementioning
confidence: 99%
“…Between 1970 and 1978, nonmetropolitan cpunties gained an additional 619,000 manufacturing jobs an~3,452,000 service jobs (Beale, 1980 Twenty-two percent of the region's popul~tion increase between 1970 and 1975 was a result of an increase of in-migration. Morrill, Downing, and Leon (1986) and Stevens (1980) hypothesize continued infusion of in-migration to:the (Hibbard, 1989;Morrill, Downing, & Leon, 1986;Shapira & Leigh-Preston, 1984). (Hibbard, 1989;Markusen, Hall, & Glasmeier, 1986;Saxenian, 1985).…”
Section: Oregonmentioning
confidence: 99%